RANCANG BANGUN SISTEM PENGOLAHAN DATA POSYANDU KEMBANG SETAMAN KOTA BOGOR BERBASIS WEB - Inas Suri Dary Linandar; Safaruddin Hidayat Al-Ikhsan; Berlina Wulandari (INFOTECH journal, 2024)
Posyandu is a health effort carried out by, from and with the community. In the posyandu there are several activities carried out by cadres, such as maternal and child health, family planning programs, and pregnancy checks. The aim of building a data processing information system for Posyandu Kembang Setaman is specifically for mothers and children. However, there is a problem in this research, namely how to build a system that is able to provide services and report the results of weighing, immunization, mothers who carry out family planning programs and pregnancy checks. The solution to this problem is to simplify data collection on inspection results, and simplify services without using KMS. In this research the author used the waterfall research method. This activity requires a Posyandu Information System to make it easier to process patient examination data. Data was obtained from this research by conducting interviews with posyandu cadres. The data that has been obtained will be identified, designed and then implemented and system tested. To design the interaction between the user and the system, it is depicted using a UML diagram to make it easier to build this information system. The design of the Posyandu Kembang Setaman data processing system can make it easier for cadres and other officers to report the latest patient input, search for patients and process patient data and produce patient visit data.